English Language Learning Experiences in Selecting Youtube Video - Isni Yulia Nur; Endang Susilawati; Surmiyati; Regina; Eusabinus Bunau (Universitas Muhammadiyah Kalimantan Timur, 2025)
YouTube can be a valuable tool for enhancing students' understanding of the English language, as it is well-recognized as a website that offers a diverse range of videos across many contexts. YouTube is a valuable and accessible resource for learning English due to its wide collection of instructional videos (Khoiroh, 2021). This research aims to determine the criteria for selecting YouTube videos, the challenges, and the impact of using YouTube videos to learn speaking and listening skills through descriptive qualitative research. The participants of this research are four students from class A+ sixth-semester English education regular-A students at Universitas Tanjungpura in the 2023/2024 academic year. The interview was used in data collection and analyzed using qualitative analysis techniques. Based on the participants' experiences, they use YouTube videos to learn English, such as improving their speaking and listening skills, using audio quality, native speakers, daily conversation context, subtitles, and video duration as the criteria they use to select YouTube videos. Apart from that, they also used recommendations given by lecturers or friends, and they consider these videos trustworthy because they have been used before by their lecturers or friends. The participants also experienced challenges when selecting the YouTube videos they would use. The challenges include finding videos with good audio quality, dealing with poor production quality, finding relevant videos, and overcoming technical problems. Using the criteria for YouTube videos that suit the participants' needs and facing several challenges in selecting it, they still said that YouTube videos can improve their speaking and listening skills.